Triptolide Downregulates the Expression of NRF2 Target Genes by Increasing Cytoplasmic Localization of NRF2 in A549 Cells - Nam, Le Ba; Choi, Won Jun; Keum, Young-Sam (Frontiers in Pharmacology, 2021)
We have identified triptolide as a novel NRF2 inhibitor, which significantly attenuates ARE-luciferase activity at nanomolar concentrations. Triptolide did not affect the level of NRF2, but significantly inhibited the expression of NRF2 target genes in A549 cells. We found that NRF2 possesses a previously unrecognized NES in the Neh2 domain, and that triptolide promotes an interaction between NRF2 and CRM1. Triptolide also decreased nuclear accumulation of NRF2, suggesting that it promotes nuclear export of NRF2. In addition, we show that triptolide decreased the expression of NRF2 target genes and increased intracellular oxidative stress, suppressing invasion and promoting cisplatin-induced apoptosis in A549 cells. Finally, oral administration of triptolide suppressed the growth of A549 xenografts in athymic mice by decreasing the expression of NRF2 target genes and promoting oxidative damages via the nuclear export of NRF2 and CRM1 in vivo. To the best of our knowledge, triptolide is the first type of compound to inhibit NRF2 by increasing cytoplasmic localization of NRF2.